The Role of Charisma and Psychological Capital on Credibility among Start-up Entrepreneurs - Wirawan, Hillman; Tandiayuk, Suryadi (Program Pascasarjana Universitas Negeri Makassar, 2018)
This study aims to further explain the effect of Charisma and Psychological Capital (PsyCap) on Credibility among start-up entrepreneurs in Makassar City. Participants in this study were employees who worked in various Small and Medium Business Units with minimum age of 17 years. There were 132 participants involved in this study (58% female and 42% male). Using the Hierarchical Regression technique, this study found that all regression models significantly predicted the entrepreneurs’ Credibility with p value ranged from 0.01 to 0.001. Charisma could explain 31% of Credibility while together Charisma and PsyCap explained 40% of Credibility. The models showed that Charisma (β= 0.27, p< 0.01) and PsyCap (β= 0.41, p< 0.001) acted as significant predictors for the start-up entrepreneurs’ credibility. This study confirmed the previous theories and evidence regarding the effect of Charisma and PsyCap on Credibility. Both Charisma and PsyCap contributed significant effect on the start-up entrepreneurs’ credibility.